The Mechano-Stability of Isolated Focal Adhesions is Strongly Dependent on pH - Beaumont, Kristin Grant (2012)
This report demonstrates that the mechanical stability of focal adhesions exhibits a biphasic and sensitive pH dependence. These studies used isolated focal adhesions, which retain many of the properties of the intracellular structures, including protein composition and force-dependent reinforcement by cytosolic proteins. The focal adhesion structures are least stable to applied force at a pH of 6.4, and significantly more stable at slightly higher and lower pH values. This trend is consistent with previous work that characterized the pH dependence of cell migration and may therefore be relevant to controlling the invasiveness of metastatic cancer cells. This approach is significant because it allows biochemical studies of large protein complexes previously studied only in cell culture, and therefore offers new opportunities for performing mechanistic studies of a range of factors that contribute to focal adhesion stability.